Philosophy as The Foundation of Science in The Development of Chemistry - Ahmad Tohir; Suyitno Muslim; Novi Ayu Safira (Universitas Lampung, 2021)
Abstract: Philosophy As The Foundation Of Science In The Development Of Chemistry. This article aims to present an explanation of philosophy as the basis of science in the development of chemistry. This article uses the literature review method. The library sources used in this article are journals and books on the development of chemistry. The results of the research show that (1) Philosophy serves as the basis from which philosophy is obtained the truth which becomes the basis or foundation of chemistry. By learning something related to chemistry through knowledge (philosophy) is a step to get true and objective knowledge about chemistry. (2) Chemists and scientists agree on the basis of the development of chemistry, namely to obtain answers to the what and why questions about matter in nature, each of which will produce facts and theoretical knowledge about matter whose truth can be explained by mathematical logic. Finally, (3) The study of chemistry in its development includes aspects of ontology, epistemology, and axiology. The ontology aspect includes the chemical concept of matter and matter. The epistemological aspect includes the understanding of chemistry that is obtained and developed based on experiments and theories. While the axiological aspect of chemistry includes the usefulness of values for human understanding so that humans will be better at the surrounding nature and use various natural processes that take place in it to meet the needs of human life. Keywords: Philosophy, Development of ChemistryDOI: 10.23960/jppk.v10.i3.2021.19